Sustainable Development in the European Union and World Economy-Main Selected Aspects; Zroẃnowazȯny rozwoj́ w Unii Europejskiej i w gospodarcwe sẃiatowej - głoẃne wybrane aspekty - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2011)
The aim of the paper is to present key theoretical and empirical issues of sustainable development and environmental protection issues from the global and European perspective, with special reference to the implication of this concept for Central and Eastern European members of the EU. Main aspects are discussed in the paper from the EU and global perspective, with special reference to: the global partnership for sustainable development; fighting poverty and promoting social development; sustainable management of natural and environmental resources; trading in greenhouse gas emission allowances; main global and European challenges; goals and challenges facing the European Union member states as stemming from major strategic European Union renewed documents promoting sustainable development; especially promoting consumption and production that is sustainable and environmentally-friendly and green labeling system; a detailed look at "new" environmental policies; with special reference to sustainable transportation; a strategy for the sustainable use of natural resources; preventive strategy (preventing the creation of wastes) and waste recycling; sustainable and competitive tourism. – – Celem niniejszego artykułu jest przedstawienie kluczowych zagadnient́eoretycznych i empirycznych zroẃnowazȯnego rozwoju i ochrony sŕodowiska z perspektywy sẃiatowej i europejskiej, ze szczegoĺnym uwzglednieniem wpływu tej koncepcji na rozwoj́ nowych krajoẃ członkowskich UE połozȯnych w Europie Sŕodkowej i Wschodniej. Głoẃne aspekty zostały omoẃione z unijnej i globalnej perspektywy, zwłaszcza takich jak: globalne partnerstwo na rzecz zroẃnowazȯnego rozwoju, walka z ubośtwem i wspieranie rozwoju społecznego, zroẃnowazȯne zarzadzanie zasobami naturalnymi i sŕodowiskowymi, handel przydziałami na emisje gazoẃ cieplarnianych. Analizie poddane zostaly roẃniezẇyzwania stojace przed panśtwami Unii Europejskiej, wynikajace z nowych strategicznych dokumentoẃ Unii Europejskiej, majacych na celu promowanie zroẃnowazȯnego rozwoju, w tym w dziedzinie zroẃnowazȯnej produkcji konsumpcji, przyjaznego dla sŕodowiska naturalnego "zielonego " systemu etykietowania, nowych celoẃ i wyzwanẃ odniesieniu do polityki ochrony sŕodowiska, ze szczegoĺnym uwzglednieniem zroẃnowazȯnego transportu, strategii zroẃnowazȯnego wykorzystania zasoboẃ naturalnych, zapobiegania powstawaniu szkodliwych odpadoẃ i promocji recyklingu oraz rozwoju zroẃnowazȯnej i konkurencyjnej turystyki.
Keywords: 330